THE WORLD FINANCIAL AND ECONOMIC CRISIS AND ITS IMPACT ON TAJIKISTAN - HASANOV, Munim (CENTRAL ASIA AND THE CAUCASUS, 2010)
The financial crisis that started in U.S. real estate markets in late 2007 has now developed into a financial and economic crisis, spreading to most countries of the world.The signs of a financial crisis include a decline in bank liquidity, which means a loss of potential customers; rising interest rates on loans, the demand for which decreases; the bankruptcy of a certain part of credit institutions and a financial market slump.An economic crisis is characterized by a slowdown in GDP growth and a decline in GDP per capita. The supply of goods and services decreases due to a drop in their production, while demand increases; accordingly, prices go up, unemployment rises, and social tensions increase.The current crisis is the deepest one in the history of capitalism since the Great Depression of the 1930s, and its consequences will probably be felt in the medium term as well.